Group B Streptococci recto-vaginal colonization, antimicrobial susceptibility pattern, and associated factors among pregnant women at selected health facilities of Wolaita Sodo Town, Southern Ethiopia - Kumalo, Abera; Gebre, Biruk; Shiferaw, Shimelis; Wolde, Wokil; Shonde, Tamirayehu (Frontiers in Microbiology, 2023)
Background Streptococcus agalactiae or Group B Streptococcal colonization of the gastrointestinal and genital tracts of pregnant women usually remains asymptomatic, even though it is the critical determinant of infection in neonates and young infants. It causes early and late onset of invasive Group B Streptococcus (GBS) disease manifesting as septicemia, meningitis, and pneumonia. Now it is recognized as an important cause of maternal and neonatal morbidity and mortality in many parts of the world including Ethiopia, where the magnitude of the problem has been little studied. The aim of this study was to assess the prevalence of GBS colonization and to identify associated risk factors and antimicrobial susceptibility patterns among pregnant women at selected health facilities of Wolaita Sodo Town, Southern Ethiopia. Methodology A health-facility-based cross-sectional study design was conducted at WSUCSH & Wolaita Sodo Health Center from June to August, 2022. A total of 279 pregnant women who were in ANC follow-up at 35–37 weeks of gestation were included. For GBS isolation, recto-vaginal swabs were inoculated in 1 mL Todd-Hewitt broth medium supplemented with 10 μg/mL colistin and 15 μg/mL nalidixic acid, followed by identification of isolates based on colonial morphology, gram stains, catalase reaction, and CAMP tests. Antimicrobial susceptibility testing was performed using a modified Kirby–Bauer disc diffusion method. All collected data were entered in Epi info 4.6.0.2, then transferred and tabulated using SPSS version 20. Logistic regression analysis was used to see the association between variables. Finally, a p-value <0.05 was considered statistically significant. Results In the present study, 279 pregnant mothers, aged between 15 to 38 years with a mean of 26.5 ± 4.5 years, were included. Of all participants, the highest proportion (120) (43.01%) were housewives. The overall carriage rate of GBS was 67 (24.0%). GBS colonization showed a statistically significant association with college and above levels of maternal education [AOR = 6.610, 95% CI (1.724–25.349), p = 0.01]. High susceptibility of GBS isolate was seen with Penicillin G & Chloramphenicol (92.5%), Ampicillin, Ceftriaxone (89.6%), Vancomycin (74.62%), and Erythromycin (77%). Relatively, GBS showed high resistance to Tetracycline (88%). Conclusion and recommendation In this study, the overall prevalence of GBS colonization was 24.0%. College and above educational level was statistically significant with GBS colonization. This study aimed to draw attention to the management of Group B Streptococci in pregnant women by making GBS culture one of the routine diagnoses during ANC follow-up and to prevent infection with early detection.